Characterisation and antioxidant activity of glycated casein hydrolysate with xylose: Impacts of zinc sulphate and cupric chloride. (March 2021) - Wang, Xindi; Tian, Ran; Shi, Xiaohan; Hu, Jialun; Jiang, Zhanmei; Hou, Juncai
Abstract: Impacts of zinc sulphate and cupric chloride on characteristics and antioxidant capacities of glycated products (GPs) derived from casein hydrolysate (CH) and xylose were studied. The browning degree of xylose–CH GPs was the largest at zinc sulphate addition of 15 mg L −1, while its browning degree increased with cupric chloride extended from 0 to 15 mg L −1 . Loss of free amino groups, fluorescence intensity and the 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging capacity of xylose–CH GPs increased with the increase of cupric chloride addition, but loss of amino groups, fluorescence intensity and DPPH radical scavenging capacity were largest at the zinc sulphate addition of 15 mg L −1 . The addition of zinc sulphate and cupric chloride promoted production of higher and smaller molecular substances in xylose–CH GPs and CH. Therefore, zinc sulphate and cupric chloride promoted glycated reaction of xylose and CH and enhanced antioxidant activity of xylose–CH GPs.